Hydrogen-rich gas from catalytic steam gasification of eucalyptus using nickel-loaded Thai brown coal char catalyst - Phuhiran C. (2014)
Hydrogen gas production from eucalyptus by catalytic steam gasification was carried out in an atmospheric pressure of two-stage fixed bed. The gasifier was operated with the temperature range of 500-650 C and steam partial pressure of 16, 30 and 45 kPa; nickel-loaded Thai brown coal char was used as a catalyst. The yields and compositions of the gasification products depend on the operating conditions, especially, the reaction temperature and the steam. The yield of H2 increased at elevated temperatures, from 26.94 to 46.68%, while that of CO dramatically decreased, from 70.21 to 37.71 mol%. The highest H 2 yield, 46.68%, was obtained at the final gasifying temperature of 650 C. Eucalyptus catalytic steam gasification indicated that the maximum H 2/CO ratio reached 1.24 at the gasification temperature of 650 C and the steam partial pressure of 30 kPa. It can be concluded that eucalyptus is appropriate for synthesis gas production from eucalyptus volatiles by catalytic steam gasification while using nickel-loaded brown coal char as a catalyst. Copyright © 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.